Trivalent chromium incorporated in a crystalline calcium phosphate matrix accelerates materials degradation and bone formation in vivo. (15th March 2018) - Rentsch, Barbe; Bernhardt, Anne; Henß, Anja; Ray, Seemun; Rentsch, Claudia; Schamel, Martha; Gbureck, Uwe; Gelinsky, Michael; Rammelt, Stefan; Lode, Anja
Graphical abstract: Abstract: Remodeling of calcium phosphate bone cements is a crucial prerequisite for their application in the treatment of large bone defects. In the present study trivalent chromium ions were incorporated into a brushite forming calcium phosphate cement in two concentrations (10 and 50 mmol/mol β-tricalcium phosphate) and implanted into a femoral defect in rats for 3 and 6 month, non-modified brushite was used as reference. Based on our previous in vitro findings indicating both an enhanced osteoclastic activity and cytocompatibility towards osteoprogenitor cells we hypothesized a higher in vivo remodeling rate of the Cr 3+ doped cements compared to the reference. A significantly enhanced degradation of the modified cements was evidenced by micro computed tomography, X-ray and histological examinations. Furthermore the formation of new bone tissue after 6 month of implantation was significantly increased from 29% to 46% during remodeling of cements, doped with the higher Cr 3+ amount. Time of flight secondary ion mass spectrometry (ToF-SIMS) of histological sections was applied to investigate the release of Cr 3+ ions from the cement after implantation and to image their distribution in the implant region and the surrounding bone tissue. The relatively weak incorporation of chromium into the newly formed bone tissue is in agreement to the low chromium concentrations which were released from the cements in vitro. The faster degradation of the Cr 3+ doped cements was also verified by ToF-SIMS. The positive effect of Cr 3+ doping on both degradation and new bone formation is discussed as a synergistic effect of Cr 3+ bioactivity on osteoclastic resorption on one hand and improvement of cytocompatibility and solubility by structural changes in the calcium phosphate matrix on the other hand. Statement of Significance: While biologically active metal ions like strontium, magnesium and zinc are increasingly applied for the modification of ceramic bone graft materials, the present study is the first report on the incorporation of low doses of trivalent chromium ions into a calcium phosphate based biomaterial and testing of its performance in bone defect regeneration in vivo. Chromium(III)-doped calcium phosphate bone cements show improved cytocompatibility and both degradation rate and new bone formation in vivo are significantly increased compared to the reference cement. This important discovery might be the starting point for the application of trivalent chromium salts for the modification of bone graft materials to increase their remodelling rate.